2017
DOI: 10.1186/s13195-017-0236-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased dementia risk predominantly in diabetes mellitus rather than in hypertension or hyperlipidemia: a population-based cohort study

Abstract: BackgroundThe pathophysiology of insulin resistance-induced hypertension and hyperlipidemia might entail differences in dementia risk in cases with hypertension and hyperlipidemia without prior diabetes mellitus (DM). This study investigated whether incident hypertension, incident hyperlipidemia, or both, increased the dementia risk in patients with and without DM.MethodsA nationwide retrospective cohort study was conducted. The study sample was obtained from the National Health Insurance Research Database. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 40 publications
0
39
1
1
Order By: Relevance
“…BMI and long-term weight changes were divided into quintiles. We first checked the association between the demographic variables of sex, age, education level, and histories of stroke and diabetes [ 20 ] (basic determinants of MMSE-assessed cognitive impairment) and prevalence of cognitive impairment, and then ORs calculated according to potential predictors were adjusted for covariates, including sex, age, education level, and histories of stroke and diabetes. P for trend was calculated by logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…BMI and long-term weight changes were divided into quintiles. We first checked the association between the demographic variables of sex, age, education level, and histories of stroke and diabetes [ 20 ] (basic determinants of MMSE-assessed cognitive impairment) and prevalence of cognitive impairment, and then ORs calculated according to potential predictors were adjusted for covariates, including sex, age, education level, and histories of stroke and diabetes. P for trend was calculated by logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus is a metabolic disorder characterized by insulin resistance or insulin deficiency. During diabetes variations in plasma osmotic pressure and oxidative stress levels may result in cognitive changes in the brain, that is, the imbalance between oxidants and antioxidants initiates neurodegeneration through the excessive deposition of Aβ peptide and the release of free radicals, and, correspondingly, they can lead to dementia [ 80 , 81 ]. The preliminary results of recent clinical trial studies have indicated that intranasal insulin therapy may help improve verbal memory, especially, the story recall performance of the APOE genotype [ 82 ].…”
Section: Other Established (Non-)modifiable Risk Factors and Possimentioning
confidence: 99%
“…We remind the reader that, for instance, midlife obesity is often associated with hypertension and diabetes mellitus. These three possibly modifiable risk factors can cause an accumulation of neurotoxic peptides and oxidative stress level changes in the brain that in time may result in cognitive impairment and dementia [ 78 , 81 , 89 ]. Similarly, the higher risk of dementia in the elderly individuals with various comorbid cardiometabolic diseases such as diabetes mellitus or stroke can be moderated by social engagement and physical activities [ 131 ].…”
Section: Future Possible Research Directions and Trends In The Trementioning
confidence: 99%
“…In a recent retrospective cohort study using the National Insurance Research Database of about 10,000 patients with diabetes and 50,000 age and sex matched non-diabetic patients, researchers found that dementia risk was higher in diabetics and the risk did not significantly increase in the presence of hypertension and hyperlipidemia. However, in the non-diabetes cohort, patients who had both hypertension and hyperlipidemia had a higher risk of dementia compared to those without (Fan Y-C et al, 2017). This study sheds light on the complexity of vascular risk factors and whether they are perhaps meditated through one main mechanism (ex: insulin resistance) without really having an independent effect on dementia risk.…”
Section: Hypertensionmentioning
confidence: 78%